Brain Metastases from Endometrial Carcinoma - Ettie Piura; Benjamin Piura (2012)
This paper will focus on knowledge related to brain metastases from endometrial carcinoma. To date, 115 cases were documented in the literature with an incidence of 0.6% among endometrial carcinoma patients. The endometrial carcinoma was usually an advanced-stage and high-grade tumor. In most patients ( ~ 90%), brain metastasis was detected after diagnosis of endometrial carcinoma with a median interval from diagnosis of endometrial carcinoma to diagnosis of brain metastases of 17 months. Brain metastasis from endometrial carcinoma was either an isolated disease limited to the brain only ( ~ 50%) or part of a disseminated disease involving also other parts of the body ( ~ 50%). Most often, brain metastasis from endometrial carcinoma affected the cerebrum ( ~ 75%) and was solitary ( ~ 60%). The median survival after diagnosis of brain metastases from endometrial carcinoma was 5 months; however, a significantly better survival was achieved with multimodal therapy including surgical resection or stereotactic radiosurgery followed by whole brain radiotherapy (WBRT) and/or chemotherapy compared to WBRT alone. It is suggested that brain imaging studies should be considered in the routine follow up of patients with endometrial carcinoma and that the search for a primary source in females with brain metastases of unknown primary should include endometrial biopsy.